Farming practices and crop varietal choice among Ugandan bean and sweet potato producers - LaRochelle, Catherine; Labarta, Ricardo; Katungi, Enid; Herrington, Caitlin; Asare-Marfo, Dorene; Ball, Anna-Marie; Birol, Ekin; Alwang, Jeffrey (International Food Policy Research Institute, 2018)
The common bean, Phaseolus vulgaris, and white- or yellow-fleshed sweet potatoes, Ipomoea batatas, are widely grown in Uganda as both food and cash crops. Beans and sweet potatoes are common staples in Uganda, providing hearty, affordable nourishment to rural households. However, throughout the country, iron and vitamin A deficiency (VAD) remain high. Diets low in iron intake are a major cause of iron-deficiency anemia, which is associated with fatigue, decreased productivity, and reduced immune function. Childhood anemia is associated with impaired mental and physical development. Among pregnant women, anemia may lead to premature delivery and low birth weight (WHO 2008). VAD further impedes child growth, contributes to blindness, lessens immune function, and increases the morbidity and mortality of children and pregnant women (WHO 2009). According to data from the Uganda Demographic and Health Survey 2011 (the most recent available), 49 percent of children ages six months to five years and 24 percent of women between the ages of 15 and 49 years suffer from anemia; for VAD, those statistics are 38 percent of children and 36 percent of women (UBOS 2012).